Cholesteric liquid crystal film and its manufacturing method
The cholesteric liquid crystal film with a stripe pattern and folded structure on one surface addresses the limitation of uniform orientation states by achieving differential light scattering, enabling innovative applications.
Patent Information
- Application Number
- JP2021574539
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2020-12-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-12-21
AI Technical Summary
Existing cholesteric liquid crystal films have uniform orientation states on both sides, limiting their applications due to lack of differential light scattering performance between the front and back sides.
A cholesteric liquid crystal film with a stripe pattern and a folded structure on one surface, where the dark parts of the striped pattern are inclined relative to the main surface at an angle of 20° to 90°, and the folding structure exists in the surface layer up to 1/3 of the film thickness.
The film achieves differential light scattering performance between the front and back sides, enabling applications such as transparent screens and electronic signs that utilize specific directional light scattering.
Smart Images

Figure 0007662541000011 
Figure 0007662541000012 
Figure 0007662541000013
Abstract
Description
[Technical field]
[0001] The present disclosure relates to cholesteric liquid crystal films and methods for making same. [Background technology]
[0002] It is known that a cholesteric liquid crystal film exhibits a striped pattern of dark and light areas when observed under a microscope.
[0003] For example, FIG. 6 of WO 2018 / 043678 shows a SEM photograph of a cross section of a cholesteric liquid crystal film, in which a striped pattern of dark and light areas can be seen.
[0004] For example, FIG. 5 of JP-A-2005-37735 shows a photograph of the cross-sectional structure of a cholesteric liquid crystal polarized selective reflection layer taken by a transmission electron microscope, in which a striped pattern of dark and light areas is observed. Summary of the Invention [Problem to be solved by the invention]
[0005] The striped pattern of dark and light areas in the cholesteric liquid crystal film indicates the alignment state of the cholesteric liquid crystal. If the orientation state of the cholesteric liquid crystal differs between the front and back sides despite being a single layer, it is expected that the cholesteric liquid crystal film will have a wider range of uses.
[0006] Therefore, the present disclosure has been made in consideration of the above circumstances. An object of one embodiment of the present disclosure is to provide a cholesteric liquid crystal film in which the alignment state of cholesteric liquid crystal differs between the front side and the back side, and a method for producing the same. [Means for solving the problem]
[0007] Specific means for solving the problems include the following aspects. <1> It comprises a cholesteric liquid crystal, and A cholesteric liquid crystal film having a striped pattern of alternating dark and light areas in a cross section in the thickness direction observed under a microscope, and a folded structure of dark areas in the surface layer part of one of a pair of principal surfaces. <2> In the cross section, the dark areas in the striped pattern are inclined with respect to the main surface. <1> The cholesteric liquid crystal film according to claim 1. <3> The inclination angle of the dark portions of the striped pattern with respect to the principal surface is 20° to 90°. <2> The cholesteric liquid crystal film according to claim 1. <4> the folded structure formed by the dark portion is present in a region extending from the one principal surface to 1 / 3 of the film thickness; <1> ~ <3> 13. A cholesteric liquid crystal film according to any one of claims 1 to 12. <5> In the surface layer portion of the one principal surface, the folded structure formed by the dark portions is present in 2 to 10 locations among 20 adjacent dark portions. <1> ~ <4> 13. A cholesteric liquid crystal film according to any one of claims 1 to 12. <6> In a surface layer portion of the other of the pair of principal surfaces, the folded structure formed by the dark portions does not exist or exists in less than two places among 20 adjacent dark portions. <1> ~ <5> 13. A cholesteric liquid crystal film according to any one of claims 1 to 12. <7> A first step of applying a coating liquid containing a solvent, a liquid crystal compound, and a chiral agent onto a substrate to form a coating film; A second step of applying a shear force to the formed coating surface with a blade; having The shear rate in the second step is 1000 s -1 This is the method for producing a cholesteric liquid crystal film. Effect of the Invention
[0008] According to an embodiment of the present disclosure, there is provided a cholesteric liquid crystal film in which the alignment state of cholesteric liquid crystal differs between the front side and the back side, and a method for producing the same. [Brief description of the drawings]
[0009] [Figure 1] 1 is an example of a microscope photograph of a cross section in the thickness direction of a cholesteric liquid crystal film according to the present disclosure. [Diagram 2] 1 is a schematic diagram showing an example of a molecular arrangement of rod-shaped liquid crystal compounds in a cross section of a cholesteric liquid crystal film. FIG. [Diagram 3] 1A to 1C are schematic diagrams illustrating an example of a method for producing a cholesteric liquid crystal film according to the present disclosure. [Figure 4] 1 is a microscope photograph of a cross section in the thickness direction of the cholesteric liquid crystal film of Example 1. [Diagram 5] 1 is a microscope photograph of a cross section in the thickness direction of the cholesteric liquid crystal film of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present disclosure will be described in detail. The present disclosure is not limited to the following embodiments, and can be implemented with appropriate modifications within the scope of the object of the present disclosure.
[0011] When describing the embodiments of the present disclosure with reference to the drawings, the description of the same components and reference numerals in the drawings may be omitted. Components indicated by the same reference numerals in the drawings are the same components. The dimensional ratios in the drawings do not necessarily represent the actual dimensional ratios.
[0012] In the present disclosure, a numerical range indicated using "~" indicates a range including the numerical values described before and after "~" as the lower and upper limits, respectively. In the numerical ranges described in stages in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples.
[0013] In the present disclosure, when a plurality of substances corresponding to each component are present in the coating liquid, the amount of each component in the coating liquid means the total amount of the plurality of substances present in the coating liquid, unless otherwise specified.
[0014] In the present disclosure, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.
[0015] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments.
[0016] In this disclosure, the term "principal surface" refers to a surface that occupies a major area of the surface of an object, and the term "a pair of principal surfaces" refers to the front and back surfaces of a film-like object such as a cholesteric liquid crystal film. From the viewpoint of manufacturing, the "pair of main surfaces" are preferably arranged parallel to each other. Here, "parallel to each other" means that the angle between one main surface and the other main surface is less than ±5°.
[0017] In the present disclosure, "molecular axis" refers to an axis passing through the center of a molecular structure along the longitudinal direction of the molecular structure, except that "molecular axis" when used in reference to a discotic liquid crystal compound refers to an axis perpendicular to the discotic plane of the discotic liquid crystal compound.
[0018] In the present disclosure, the term "solid content" refers to all components of a target object excluding the solvent. In the present disclosure, the "mass of solid content" means the mass of the object excluding the mass of the solvent.
[0019] <Cholesteric liquid crystal film> The cholesteric liquid crystal film according to the present disclosure is a cholesteric liquid crystal film that contains cholesteric liquid crystals and has, in a cross section in the thickness direction observed under a microscope, a striped pattern in which dark and light areas are arranged alternately, and a folded structure of dark areas in a surface layer portion of one of a pair of principal surfaces. In other words, when a cross section in the thickness direction of the cholesteric liquid crystal film according to the present disclosure is observed under a microscope, a striped pattern of alternating dark and light areas and a folded structure of dark areas on the surface layer of one of the pair of principal surfaces are seen on the cross section. Here, the "cross section in the thickness direction" refers to a cross section obtained when the cholesteric liquid crystal film is cut along the thickness direction.
[0020] The cholesteric liquid crystal film according to the present disclosure can be said to be a cholesteric liquid crystal film in which the orientation state of the cholesteric liquid crystal differs between the front side and the back side, since a cross section in the thickness direction observed under a microscope has a striped pattern and a folded structure on the surface layer of one of the pair of main surfaces, as described above. In this way, since a folded structure caused by dark areas is seen in the surface layer portion of one of the main surfaces, it is presumed that, for example, the light scattering performance, etc. differs between the main surface side on which the folded structure is seen and the other main surface side. As a result, it is believed that the film can be used in applications that utilize the difference in light scattering performance between the front and back sides. For example, if a folded structure due to a dark area is observed in the surface layer of one of the main surfaces, the function of scattering light only in a specific direction may be exhibited on the other main surface side. A cholesteric liquid crystal film with such a function can be used in transparent screens, lighting, electronic signs, etc.
[0021] In the cross-section photographed by a microscope as described in the above-mentioned International Publication No. 2018 / 043678 and JP 2005-37735 A, a striped pattern of alternating dark and light areas is observed, but the folded structure of the dark areas is present in the center in the thickness direction, and does not have the configuration of the cholesteric liquid crystal film according to the present disclosure.
[0022] [Cholesteric Liquid Crystal] The cholesteric liquid crystal film according to the present disclosure includes cholesteric liquid crystals. Cholesteric liquid crystal has a layered structure consisting of layers of liquid crystal compound molecules. In each layer, the molecules of the liquid crystal compound are aligned in a fixed direction (i.e., the molecular axes are aligned in a fixed direction), and the alignment direction of the molecules in each layer shifts so that they rotate helically as they proceed in the stacking direction, forming a helical structure. The axis of this helical structure is called the helical axis of the cholesteric liquid crystal.
[0023] [Microscopic observation of cross section in thickness direction] As described above, the cholesteric liquid crystal film according to the present disclosure has a striped pattern and a folded structure in a cross section in the thickness direction observed under a microscope. For microscopic observation, a scanning electron microscope (also called SEM) or a polarizing microscope is used. For microscopic observation, a scanning electron microscope (SEM) or a polarizing microscope may be used depending on the pitch of the stripe pattern (i.e., the distance between dark areas or the distance between light areas). To obtain a cross section in the thickness direction, the cholesteric liquid crystal film may be cut, for example, using a microtome. The cross section in the thickness direction may be observed at 18 points (i.e., 180°) by rotating the cut surface in 10° increments. It is sufficient if the striped pattern and folded structure are observed at least at one of the 18 points. Here, the area of the cross section to be observed is, for example, at least 1000 μm 2 Let us assume that. In the present disclosure, a "striped pattern" is defined as a pattern in which at least 10 dark and light lines (preferably at least 20 lines) are alternately arranged in the above-mentioned microscope observation.
[0024] (Striped) In the cholesteric liquid crystal film according to the present disclosure, a cross section in the thickness direction observed under a microscope has a striped pattern in which dark and light areas are arranged alternately. The striped pattern will be described with reference to Fig. 1. Here, Fig. 1 is an example of a microscope photograph of a cross section in the thickness direction of a cholesteric liquid crystal film according to the present disclosure. FIG. 1 is a micrograph of a laminate having a cholesteric liquid crystal film 1 according to the present disclosure on an alignment layer of a substrate 3 having an alignment layer 2, in which the cholesteric liquid crystal film 1 has a striped pattern of alternating dark areas 10 and light areas 20. In the cholesteric liquid crystal film 1 shown in FIG. 1, the dark areas 10 are arranged at equal intervals, and the light areas 20 are also arranged at equal intervals.
[0025] The dark and light areas seen by microscopic observation appear because the direction of the molecular axis of the liquid crystal compound that forms a helical structure changes with respect to the cross section observed by the microscope. For example, when a cholesteric liquid crystal film containing rod-shaped liquid crystal compounds is observed with a polarizing microscope, the areas in which the molecular axes of the rod-shaped liquid crystal compounds are oriented perpendicular to the cross section observed with the microscope (including areas close to perpendicular; the same applies below) appear relatively bright. On the other hand, when a cholesteric liquid crystal film containing rod-like liquid crystal compounds is observed with a polarizing microscope, the areas where the molecular axes of the rod-like liquid crystal compounds are parallel (or nearly parallel) to the cross section observed with the microscope appear relatively dark. The alternating arrangement of the two regions described above results in a striped pattern of alternating light and dark areas.
[0026] The molecular axis of the liquid crystal compound will now be described in more detail. When dark and light areas are observed in a cross section in the thickness direction under a microscope, it is considered that the molecules of the liquid crystal compound in the cholesteric liquid crystal film are aligned, for example, as shown in Fig. 2. Here, Fig. 2 is a schematic diagram showing an example of the molecular alignment of a rod-shaped liquid crystal compound in a cross section of a cholesteric liquid crystal film. The cholesteric liquid crystal film 1 shown in Fig. 2 has a pair of principal surfaces (i.e., principal surfaces Fa and Fb) and contains rod-like liquid crystal compounds 30, which are represented by ellipses. The rod-like liquid crystal compounds 30 are in the form of cholesteric liquid crystals and are aligned in a helical shape along a helical axis HA. In other words, since the rod-like liquid crystal compounds 30 in the cholesteric liquid crystal film 1 are arranged in a helical shape, the direction of the molecular axis 30A relative to the cross section observed by the microscope changes along the helical axis. In Fig. 2, the state in which the molecular axis 30A is perpendicular to the cross section observed by the microscope is shown by an ellipse with a short major axis representing the rod-like liquid crystal compound 30, and the state in which the molecular axis 30A is parallel to the cross section observed by the microscope is shown by an ellipse with a long major axis representing the rod-like liquid crystal compound 30.
[0027] 2, the molecules of the rod-shaped liquid crystal compound 30 are arranged, so that a region in which the molecular axis 30A of the rod-shaped liquid crystal compound 30 is parallel to the cross section observed under a microscope (i.e., a region in which the major axis of the ellipse representing the rod-shaped liquid crystal compound 30 is long) is observed as a dark area. For the same reason, a region in which the molecular axis 30A of the rod-shaped liquid crystal compound 30 is perpendicular to the cross section observed under a microscope (i.e., a region in which the ellipse representing the rod-shaped liquid crystal compound 30 is short) is observed as a bright area.
[0028] In the cholesteric liquid crystal film 1 shown in FIG. 2, the helical axis HA is perpendicular to the molecular axis 30A of the rod-like liquid crystal compound 13 and is inclined with respect to each of the principal surfaces Fa and Fb of the cholesteric liquid crystal film 1. By tilting the helical axis HA in this way, the dark parts in the striped pattern will be tilted with respect to the main surface, as will be described later. The inclination angle of the helical axis HA with respect to the principal planes Fa and Fb is perpendicular to the inclination angle of the dark portions of the striped pattern with respect to the principal planes.
[0029] The dark areas in the striped pattern are preferably inclined with respect to the main surface. That is, it is preferable that the dark portions 10 in the striped pattern are inclined with respect to the principal surfaces Fa and Fb as shown in Fig. 1. By inclining the dark portions, the striped pattern itself is also inclined, and the reflected light caused by the cholesteric liquid crystal can be strongly emitted in a direction inclined with respect to the perpendicular direction of the principal surfaces. In the present disclosure, the aspect that "the dark portion is inclined with respect to the main surface" means that in a cross section in the thickness direction observed with a microscope, the dark portion and the main surface are not parallel to each other. More specifically, the inclination angle of the dark portions in the striped pattern with respect to the principal surface is preferably 20° to 90°, more preferably 30° to 90°, and further preferably 40° to 90°.
[0030] The inclination angle of the dark portion with respect to the principal surface is determined by the following method. In observing the cross section in the thickness direction with a microscope, the angle θ between the main surface and a straight line passing through the center of the width direction at both ends in the longitudinal direction is measured for any one dark part. Here, the dark part for which the angle θ is measured is selected from those that do not form a folded structure. Except for the case where the angle θ is 90°, the smaller angle (i.e., the acute angle) at the intersection is taken as the inclination angle. This measurement is performed for 10 dark parts, and the arithmetic average value of the measured values for the 10 dark parts is taken as the inclination angle of the dark part with respect to the main surface.
[0031] From the viewpoint of ease of formation of a helical structure in the cholesteric liquid crystal, the distance between dark areas in the striped pattern is preferably 0.01 μm to 500 μm, more preferably 0.05 μm to 100 μm, and further preferably 0.1 μm to 5 μm.
[0032] The distance between dark areas is determined by the following method. In observing the cross section in the thickness direction with a microscope, the shortest distance between five pairs of adjacent dark areas is measured. More specifically, six adjacent dark areas are first selected, and five pairs of adjacent dark areas are extracted from these six dark areas. Then, as the shortest distance between adjacent dark areas, the shortest distance between the center of one dark area in the width direction and the center of the other dark area in the width direction within the group is measured. This measurement is performed for five groups, and the arithmetic average value of the measured values for the five groups is taken as the distance between the dark areas.
[0033] It is preferable that the dark areas in the striped pattern are spaced at equal intervals. Here, "equally spaced" does not have to be completely equally spaced; it is sufficient that the values of the five shortest distances between adjacent dark areas measured when calculating the distance between dark areas are within ±10% of the distance between dark areas (i.e., the arithmetic mean value).
[0034] (Folded structure) In the cholesteric liquid crystal film according to the present disclosure, a cross section in the thickness direction observed with a microscope has a folded structure with dark areas in the surface layer portion of one of the pair of principal surfaces. The folded structure refers to a structure in which adjacent or adjacent dark areas are joined together. More specifically, as shown in FIG. 1, the folded structure 12 refers to a structure in which adjacent or adjacent dark areas are joined together to form a U-shape. In the cholesteric liquid crystal film according to the present disclosure, the above-described folded structure is observed in the surface layer portion of one of the pair of principal surfaces. It is preferable that the dark portion having a folded structure in the surface layer portion of one of the pair of principal surfaces does not have a folded structure in the surface layer portion of the other principal surface.
[0035] Here, the surface layer portion refers to the region excluding the central portion in the thickness direction of the cholesteric liquid crystal film, specifically, the region from the main surface to 1 / 3 of the film thickness. That is, in the cholesteric liquid crystal film according to the present disclosure, the folded structure (i.e., the U-shaped portion) exists in the region from one of the pair of main surfaces of the cholesteric liquid crystal film to 1 / 3 of the film thickness. More specifically, referring to FIG. 1, the folded structure (that is, the U-shaped portion) 12 exists in a region from the main surface Fb of the cholesteric liquid crystal film 1 to ⅓ of the film thickness t. The folded structure varies depending on the film thickness of the cholesteric liquid crystal film, but may be present in a region extending from one of a pair of main surfaces of the cholesteric liquid crystal film to 1 / 4 of the film thickness, or may be present in a region extending from one of a pair of main surfaces of the cholesteric liquid crystal film to 1 / 5 of the film thickness.
[0036] From the viewpoint of easily realizing the optical performance obtained by the folded structure, it is preferable that the folded structure of dark areas in the surface layer portion of one of the main surfaces is present in 2 to 10 locations among 20 adjacent dark areas, more preferably 3 to 10 locations, and even more preferably 5 to 10 locations.
[0037] In the cholesteric liquid crystal film according to the present disclosure, it is preferable that the folded structure due to the dark portion in the surface layer of the other of the pair of main surfaces (i.e., the main surface opposite to the one main surface having the folded structure in the surface layer portion) does not exist or exists in less than two places among 20 adjacent dark portions, and it is more preferable that the folded structure does not exist. That is, in the cholesteric liquid crystal film according to the present disclosure, the above-mentioned folded structure is not observed, or if observed, is very small, in the surface layer portion of the other of the pair of principal surfaces. More specifically, referring to FIG. 1, it is preferable that the folded structure (that is, the U-shaped portion) 12 does not exist in the region from the main surface Fa of the cholesteric liquid crystal film 1 to ⅓ of the film thickness t.
[0038] The number of folded structures is determined by the following method. In observing a cross section in the thickness direction with a microscope, 100 adjacent dark areas are extracted from the surface layer (i.e., the region from the main surface to 1 / 3 of the film thickness), and the number of folded structures among these 20 dark areas is determined. The dark areas to be extracted are changed, and the number of aliasing structures is calculated three times in the same manner. The arithmetic mean value of the obtained values is regarded as the number of aliasing structures.
[0039] [Components contained in cholesteric liquid crystal film] The components contained in the cholesteric liquid crystal film according to the present disclosure will be described below. The cholesteric liquid crystal film according to the present disclosure includes a liquid crystal compound that forms a cholesteric liquid crystal. Furthermore, the cholesteric liquid crystal film according to the present disclosure may contain other components (for example, a chiral agent, a solvent, an alignment regulator, a polymerization initiator, a leveling agent, an alignment assistant, a sensitizer, etc.) as necessary.
[0040] (liquid crystal compound) The liquid crystal compound contained in the cholesteric liquid crystal film according to the present disclosure is not particularly limited. For example, a known liquid crystal compound that forms a cholesteric liquid crystal can be used as the liquid crystal compound.
[0041] The liquid crystal compound may have a polymerizable group. The liquid crystal compound may have one type of polymerizable group alone, or two or more types of polymerizable groups. When the liquid crystal compound has a polymerizable group, the liquid crystal compound can be polymerized. By polymerizing the liquid crystal compound, the stability of the cholesteric liquid crystal can be improved.
[0042] Examples of the polymerizable group include a group having an ethylenically unsaturated double bond, a cyclic ether group, and a nitrogen-containing heterocyclic group capable of undergoing a ring-opening reaction.
[0043] Examples of the group having an ethylenically unsaturated double bond include an acryloyl group, a methacryloyl group, an acryloyloxy group, a methacryloyloxy group, a vinyl group, a vinylphenyl group, and an allyl group.
[0044] Examples of the cyclic ether group include an epoxy group and an oxetanyl group.
[0045] An example of a nitrogen-containing heterocyclic group capable of undergoing a ring-opening reaction is an aziridinyl group.
[0046] The polymerizable group is preferably at least one selected from the group consisting of a group having an ethylenically unsaturated double bond and a cyclic ether group.Specifically, the polymerizable group is preferably at least one selected from the group consisting of an acryloyl group, a methacryloyl group, an acryloyloxy group, a methacryloyloxy group, a vinyl group, a vinylphenyl group, an allyl group, an epoxy group, an oxetanyl group, and an aziridinyl group, more preferably at least one selected from the group consisting of an acryloyl group, a methacryloyl group, an acryloyloxy group, and a methacryloyloxy group, and particularly preferably at least one selected from the group consisting of an acryloyloxy group and a methacryloyloxy group.
[0047] Liquid crystal compounds are classified into, for example, rod-shaped liquid crystal compounds and discotic liquid crystal compounds according to their chemical structures. Rod-shaped liquid crystal compounds are known as liquid crystal compounds having a rod-shaped chemical structure. For example, known rod-shaped liquid crystal compounds can be used as the rod-shaped liquid crystal compounds. Discotic liquid crystal compounds are known as liquid crystal compounds having a discotic chemical structure. For example, known discotic liquid crystal compounds can be used as the discotic liquid crystal compounds.
[0048] From the viewpoint of adjusting the optical properties (particularly the light diffraction properties) of the cholesteric liquid crystal film, the liquid crystal compound is preferably a rod-shaped liquid crystal compound, and more preferably a rod-shaped thermotropic liquid crystal compound.
[0049] The rod-shaped thermotropic liquid crystal compound is a compound that has a rod-shaped chemical structure and exhibits liquid crystallinity in a specific temperature range. As the rod-shaped thermotropic liquid crystal compound, for example, a known rod-shaped thermotropic liquid crystal compound can be used.
[0050] Examples of the rod-shaped thermotropic liquid crystal compound include those described in Makromol. Chem., Vol. 190, p. 2255 (1989); Advanced Materials 5, p. 107 (1993), U.S. Pat. No. 4,683,327, U.S. Pat. No. 5,622,648, U.S. Pat. No. 5,770,107, WO 95 / 22586, WO 95 / 24455, WO 97 / 00600, WO 98 / 23580, WO 98 / 52905, JP-A-1-272551, JP-A-6-16616, JP-A-7-110469, JP-T-11-513019, JP-T-11-80081, JP-A-2001-328973, or JP-A-2007-279688. Examples of the rod-shaped thermotropic liquid crystal compound include the liquid crystal compound represented by General Formula 1 in JP-A-2016-81035 and the compound represented by General Formula (I) or General Formula (II) in JP-A-2007-279688.
[0051] The rod-shaped thermotropic liquid crystal compound is preferably a compound represented by the following general formula (1).
[0052] [ka]
[0053] In general formula (1), Q 1 , and Q 2 each independently represents a polymerizable group; L 1 , L 2 , L 3 , and L 4 each independently represents a single bond or a divalent linking group; A 1 , and A 2 each independently represents a divalent hydrocarbon group having 2 to 20 carbon atoms, and M represents a mesogenic group.
[0054] In general formula (1), Q 1 , and Q 2 Examples of the polymerizable group represented by the formula Q include the polymerizable groups described above. 1 , and Q 2 The preferred embodiments of the polymerizable group represented by the formula (I) are the same as those of the polymerizable group described above.
[0055] In general formula (1), L 1 , L 2 , L 3 , and L 4 is preferably a divalent linking group selected from the group consisting of -O-, -S-, -CO-, -NR-, -CO-O-, -O-CO-O-, -CO-NR-, -NR-CO-, -O-CO-, -O-CO-NR-, -NR-CO-O-, and NR-CO-NR-. R in the above divalent linking group represents an alkyl group having 1 to 7 carbon atoms, or a hydrogen atom.
[0056] In general formula (1), L 3 , and L 4 At least one of the groups is preferably -O-CO-O-.
[0057] In general formula (1), Q 1 -L 1 - and Q 2 -L 2 Each - is preferably independently CH2=CH-CO-O-, CH2=C(CH3)-CO-O-, or CH2=C(Cl)-CO-O-, and more preferably CH2=CH-CO-O-.
[0058] In general formula (1), A 1 , and A 2 The divalent hydrocarbon group represented by the formula (I) is preferably an alkylene group having 2 to 12 carbon atoms, an alkenylene group having 2 to 12 carbon atoms, or an alkynylene group having 2 to 12 carbon atoms, and more preferably an alkylene group having 2 to 12 carbon atoms. The divalent hydrocarbon group is preferably linear. The divalent hydrocarbon group may contain oxygen atoms that are not adjacent to each other, or sulfur atoms that are not adjacent to each other. The divalent hydrocarbon group may have a substituent. Examples of the substituent include halogen atoms (e.g., fluorine, chlorine, and bromine), a cyano group, a methyl group, and an ethyl group.
[0059] In general formula (1), the mesogenic group represented by M is a group that forms the main skeleton of the liquid crystal compound that contributes to the formation of liquid crystals. For the mesogenic group represented by M, for example, the description in "Flussige Kristalle in Tabellen II" (VEB Deutsche Verlag fur Grundstoff Industrie, Leipzig, published in 1984) (particularly pages 7 to 16) and the description in "Liquid Crystal Handbook" (edited by Liquid Crystal Handbook Editorial Committee, Maruzen, published in 2000) (particularly Chapter 3) can be referred to.
[0060] In the general formula (1), specific examples of the structure of the mesogenic group represented by M include the structures described in paragraph
[0086] of JP-A-2007-279688.
[0061] In general formula (1), the mesogenic group represented by M is preferably a group containing at least one cyclic structure selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups, and alicyclic hydrocarbon groups, and more preferably a group containing an aromatic hydrocarbon group.
[0062] In general formula (1), the mesogenic group represented by M is preferably a group containing 2 to 5 aromatic hydrocarbon groups, and more preferably a group containing 3 to 5 aromatic hydrocarbon groups.
[0063] In general formula (1), the mesogenic group represented by M preferably contains 3 to 5 phenylene groups, and the phenylene groups are linked to each other via -CO-O-.
[0064] In general formula (1), the cyclic structure (e.g., aromatic hydrocarbon group, heterocyclic group, and alicyclic hydrocarbon group) contained in the mesogenic group represented by M may have a substituent. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms (e.g., a methyl group).
[0065] Specific examples of the compound represented by general formula (1) are shown below. However, the compound represented by general formula (1) is not limited to the compounds shown below. In the chemical structures of the compounds shown below, "-Me" represents a methyl group.
[0066] [ka]
[0067] [ka]
[0068] Specific examples of the rod-shaped thermotropic liquid crystal compound are shown below, however, the rod-shaped thermotropic liquid crystal compound is not limited to the compounds shown below.
[0069] [ka]
[0070] The liquid crystal compound may be a synthetic product synthesized by a known method or a commercially available product. Commercially available liquid crystal compounds are available from, for example, Tokyo Chemical Industry Co., Ltd. and Fujifilm Wako Pure Chemical Industries, Ltd.
[0071] From the viewpoint of heat resistance, the content of the liquid crystal compound is preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the cholesteric liquid crystal film. There is no upper limit to the content of the liquid crystal compound. The content of the liquid crystal compound may be determined in a range of 100% by mass or less, based on the total mass of the cholesteric liquid crystal film. When the cholesteric liquid crystal film contains components other than the liquid crystal compound, the content of the liquid crystal compound may be determined in a range of less than 100% by mass (preferably 98% by mass or less, or 95% by mass or less), based on the total mass of the cholesteric liquid crystal film. The content of the liquid crystal compound is, for example, preferably 70% by mass or more and less than 100% by mass, more preferably 80% by mass to 98% by mass, and particularly preferably 90% by mass to 95% by mass, relative to the total mass of the cholesteric liquid crystal film.
[0072] (Other ingredients) The cholesteric liquid crystal film may contain components other than the liquid crystal compound (hereinafter, referred to as "other components" in this paragraph). Examples of the other components include a chiral agent, a solvent, an alignment regulator, a polymerization initiator, a leveling agent, an alignment assistant, and a sensitizer.
[0073] [Thickness of cholesteric liquid crystal film] The thickness of the cholesteric liquid crystal film is not particularly limited and may be determined depending on the application. From the viewpoint of film strength, the thickness of the cholesteric liquid crystal film is preferably 0.5 μm or more, more preferably 1 μm or more, and particularly preferably 2 μm or more. From the viewpoint of alignment accuracy, the thickness of the cholesteric liquid crystal film is preferably 30 μm or less, more preferably 25 μm or less, and particularly preferably 20 μm or less. The thickness of the cholesteric liquid crystal film is, for example, preferably 0.5 μm to 30 μm, more preferably 1 μm to 25 μm, and particularly preferably 2 μm to 20 μm.
[0074] The thickness of the cholesteric liquid crystal film is determined by the following method. The film thickness is measured at five points in a cross section in the thickness direction by microscopic observation. The arithmetic mean value of the measured values is taken as the thickness of the cholesteric liquid crystal film.
[0075] [Other layers] The cholesteric liquid crystal film according to the present disclosure may have a laminate structure with a layer other than the cholesteric liquid crystal film in addition to the cholesteric liquid crystal film. The types of the other layers are not limited as long as they do not depart from the spirit of the present disclosure. Examples of the other layers include a substrate and an alignment layer.
[0076] (base material) The cholesteric liquid crystal film according to the present disclosure may have a laminated structure together with a substrate. The substrate is preferably a resin substrate. Examples of the resin substrate include polyester-based substrates (e.g., polyethylene terephthalate and polyethylene naphthalate), cellulose-based substrates (e.g., diacetyl cellulose and triacetyl cellulose (abbreviation: TAC)), polycarbonate-based substrates, poly(meth)acrylic-based substrates (e.g., poly(meth)acrylate (e.g., polymethyl methacrylate)), polystyrene-based substrates (e.g., polystyrene and acrylonitrile styrene copolymer), olefin-based substrates (e.g., polyethylene, polypropylene, polyolefins having a cyclic structure (e.g., norbornene structure), and ethylene propylene copolymer), polyamide-based substrates (e.g., polyvinyl chloride, nylon, and aromatic polyamide), polyimide-based substrates, polysulfone-based substrates, polyethersulfone-based substrates, polyetheretherketone-based substrates, polyphenylene sulfide-based substrates, vinyl alcohol-based substrates, polyvinylidene chloride-based substrates, polyvinyl butyral-based substrates, polyoxymethylene-based substrates, and epoxy resin-based substrates. The substrate may be a substrate containing two or more resins (i.e., a blended polymer).The substrate is preferably a cellulose-based substrate, and more preferably a substrate containing triacetyl cellulose.
[0077] From the viewpoints of manufacturability, manufacturing costs, and optical properties, the thickness of the substrate is preferably in the range of 30 μm to 150 μm, and more preferably in the range of 40 μm to 100 μm.
[0078] (Alignment layer) The cholesteric liquid crystal film according to the present disclosure may have a laminated structure in which an alignment layer is provided between a substrate and the cholesteric liquid crystal film.
[0079] As the alignment layer, for example, a known alignment layer having a function of exerting an alignment control force on a liquid crystal compound can be used. The alignment layer may be an alignment layer that generates an alignment function by applying an electric field, a magnetic field, or light irradiation.
[0080] The thickness of the alignment layer is preferably in the range of 0.1 μm to 10 μm, and more preferably in the range of 1 μm to 5 μm.
[0081] Methods for forming the alignment layer include, for example, rubbing treatment of an organic compound (preferably a polymer), oblique deposition of an inorganic compound, and formation of a layer having microgrooves.
[0082] [Application] The cholesteric liquid crystal film according to the present disclosure is expected to be applied to transparent screens, lighting, electronic signs, and the like.
[0083] <Method for manufacturing cholesteric liquid crystal film> The method for producing a cholesteric liquid crystal film according to the present disclosure is not limited as long as it is a method capable of producing a cholesteric liquid crystal film having a striped pattern of alternating dark and light areas in a cross section in the thickness direction observed under a microscope, as described above, and a folded structure of dark areas in the surface layer portion of one of a pair of principal surfaces. An example of a method for producing a cholesteric liquid crystal film according to the present disclosure will be described below, but the present disclosure is not limited to this method.
[0084] The method for producing a cholesteric liquid crystal film according to the present disclosure includes a first step of applying a coating liquid containing a solvent, a liquid crystal compound, and a chiral agent onto a substrate to form a coating film, and a second step of applying a shear force to the surface of the formed coating film with a blade, and the shear rate in the second step is 1000 s -1 That's all. Each step will now be described in detail.
[0085] [1st step] In the first step, a coating liquid containing a solvent, a liquid crystal compound, and a chiral agent is applied onto a substrate to form a coating film.
[0086] (base material) The substrate used in the first step may be, for example, the substrate described in the above "Substrate". A preferred embodiment of the substrate used in the first step is the same as the substrate described in the above "Substrate". An alignment layer may be disposed in advance on the surface of the substrate used in the first step.
[0087] (liquid crystal compound) As the liquid crystal compound contained in the coating liquid used in the first step, for example, the liquid crystal compound described in the above section "Liquid crystal compound" can be used. The preferred embodiment of the liquid crystal compound contained in the coating liquid is the same as the liquid crystal compound described in the above section "Liquid crystal compound".
[0088] The coating liquid may contain one type of liquid crystal compound alone, or two or more types of liquid crystal compounds.
[0089] The content of the liquid crystal compound is preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the solid content of the coating liquid. The upper limit of the content of the liquid crystal compound may be determined according to the content of components other than the liquid crystal compound. The content of the liquid crystal compound may be determined within a range of less than 100% by mass (preferably 98% by mass or less, or 95% by mass or less), based on the solid content of the coating liquid.
[0090] (Chiral Agent) The type of the chiral agent is not limited. As the chiral agent, for example, a known chiral agent (for example, the chiral agents described in "Liquid Crystal Device Handbook, Chapter 3, Section 4-3, Chiral Agents for TN and STN, p. 199, edited by the 42nd Committee of the Japan Society for the Promotion of Science, 1989") can be used.
[0091] Many chiral agents contain asymmetric carbon atoms. However, chiral agents are not limited to compounds containing asymmetric carbon atoms. Chiral agents can also include, for example, axially asymmetric compounds and planarly asymmetric compounds that do not contain asymmetric carbon atoms. Examples of axially asymmetric compounds or planarly asymmetric compounds include binaphthyl, helicene, paracyclophane, and derivatives thereof.
[0092] The chiral agent may have a polymerizable group. For example, a polymer having a constitutional unit derived from the chiral agent and a constitutional unit derived from the liquid crystal compound is obtained by reacting a chiral agent having a polymerizable group with a liquid crystal compound having a polymerizable group.
[0093] Examples of the polymerizable group in the chiral agent include the polymerizable group described in the above section "Liquid crystal compound". Preferred embodiments of the polymerizable group in the chiral agent are the same as those described in the above section "Liquid crystal compound". The type of the polymerizable group in the chiral agent is preferably the same as the type of the polymerizable group in the liquid crystal compound.
[0094] Examples of chiral agents exhibiting strong twisting power include those described in JP 2010-181852 A, JP 2003-287623 A, JP 2002-80851 A, JP 2002-80478 A, and JP 2002-302487 A. For the isosorbide compounds described in the above-mentioned documents, isomannide compounds having a corresponding structure can also be used as the chiral agent. For the isomannide compounds described in the above-mentioned documents, isosorbide compounds having a corresponding structure can also be used as the chiral agent.
[0095] The content of the chiral agent is preferably 0.5% by mass to 10.0% by mass, more preferably 0.8% by mass to 3.0% by mass, and particularly preferably 1.0% by mass to 3.0% by mass, based on the solid content mass of the coating liquid.
[0096] (solvent) The solvent is preferably an organic solvent. Examples of the organic solvent include amide solvents (e.g., N,N-dimethylformamide), sulfoxide solvents (e.g., dimethyl sulfoxide), heterocyclic compounds (e.g., pyridine), hydrocarbon solvents (e.g., benzene and hexane), alkyl halide solvents (e.g., chloroform, dichloromethane), ester solvents (e.g., methyl acetate and butyl acetate), ketone solvents (e.g., acetone, methyl ethyl ketone, and cyclohexanone), and ether solvents (e.g., tetrahydrofuran and 1,2-dimethoxyethane). The organic solvent is preferably at least one selected from the group consisting of alkyl halide solvents and ketone solvents, and more preferably a ketone solvent.
[0097] The coating liquid may contain one type of solvent alone, or two or more types of solvents.
[0098] The content of solids in the coating liquid is preferably 25% by mass to 40% by mass, and more preferably 25% by mass to 35% by mass, based on the total mass of the coating liquid.
[0099] (Other ingredients) The coating liquid used in the first step may contain components other than those described above, such as an alignment regulator, a polymerization initiator, a leveling agent, an alignment assistant, and a sensitizer.
[0100] -Alignment control agent- Examples of the alignment regulator include the compounds described in JP 2012-211306 A, paragraphs
[0012] to
[0030] , the compounds described in JP 2012-101999 A, paragraphs
[0037] to
[0044] , the fluorine-containing (meth)acrylate polymers described in JP 2007-272185 A, paragraphs
[0018] to
[0043] , and the compounds described in detail in JP 2005-099258 A together with their synthesis methods. The polymer described in JP 2004-331812 A, which contains more than 50 mass% of the total polymerization units of a fluoroaliphatic group-containing monomer, may be used as the alignment regulator.
[0101] The alignment control agent may also be a vertical alignment agent, such as the boronic acid compound and / or onium salt described in JP-A-2015-38598 and the onium salt described in JP-A-2008-26730.
[0102] The content of the alignment control agent is preferably more than 0 mass % and not more than 5.0 mass %, and more preferably 0.3 mass % to 2.0 mass %, based on the solid content mass of the coating liquid.
[0103] -Polymerization initiator- Examples of the polymerization initiator include a photopolymerization initiator and a thermal polymerization initiator. The polymerization initiator is preferably a photopolymerization initiator from the viewpoint of suppressing deformation of the substrate due to heat and deterioration of the coating liquid. Examples of the photopolymerization initiator include α-carbonyl compounds (e.g., compounds described in U.S. Pat. No. 2,367,661 or U.S. Pat. No. 2,367,670), acyloin ethers (e.g., compounds described in U.S. Pat. No. 2,448,828), α-hydrocarbon-substituted aromatic acyloin compounds (e.g., compounds described in U.S. Pat. No. 2,722,512), polynuclear quinone compounds (e.g., compounds described in U.S. Pat. No. 3,046,127 or U.S. Pat. No. 2,951,758), and combinations of triaryl imidazole dimers and p-aminophenyl ketones (e.g., compounds described in U.S. Pat. No. 3,512,175, and the like). No. 49367), acridine compounds (e.g., compounds described in JP-A-60-105667 or U.S. Pat. No. 4,239,850), phenazine compounds (e.g., compounds described in JP-A-60-105667 or U.S. Pat. No. 4,239,850), oxadiazole compounds (e.g., compounds described in U.S. Pat. No. 4,212,970), and acylphosphine oxide compounds (e.g., compounds described in JP-B-63-40799, JP-B-5-29234, JP-A-10-95788, or JP-A-10-29997).
[0104] The content of the polymerization initiator is preferably 0.5% by mass to 5.0% by mass, and more preferably 1.0% by mass to 4.0% by mass, based on the solid content mass of the coating liquid.
[0105] (Method of preparing coating solution) The method for preparing the coating solution used in the first step is not limited. The coating liquid may be prepared, for example, by mixing the above-mentioned components. Any known mixing method may be used as the mixing method. In the coating liquid preparation method, the above-mentioned components may be mixed, and then the resulting mixture may be filtered.
[0106] [Application method] The method for applying the coating liquid is not limited. Examples of methods for applying the coating liquid include an extrusion die coater method, a curtain coating method, a dip coating method, a spin coating method, a print coating method, a spray coating method, a slot coating method, a roll coating method, a slide coating method, a blade coating method, a gravure coating method, and a wire bar method.
[0107] [Coating thickness] The thickness of the coating (i.e., the amount of the coating solution applied) is not limited. The thickness of the coating film may be determined, for example, according to the desired thickness of the cholesteric liquid crystal film, or the thickness of the coating film before the shear force described in the section "Second Step" below is applied.
[0108] [Second process] In the second step, a shear force is applied to the coating surface formed in the first step by a blade. The shear rate in the second step is 1000 s -1 That's all.
[0109] (Shear force applied by blade) In the method of applying shear force to the surface of the coating film using a blade, it is preferable to scrape off the surface of the coating film using the blade. In the above method, the thickness of the coating film may change before and after the application of shear force. The thickness of the coating film after the shear force is applied by the blade may be 1 / 2 or less, or 1 / 3 or less, of the thickness of the coating film before the shear force is applied. The thickness of the coating film after the shear force is applied by the blade is preferably 1 / 4 or more of the thickness of the coating film before the shear force is applied.
[0110] The material of the blade is not limited, and may be, for example, metal (e.g., stainless steel) and resin (e.g., Teflon (registered trademark) and polyetheretherketone (PEEK)).
[0111] The shape of the blade is not limited, and may be, for example, a plate shape.
[0112] The blade is preferably a metal plate-like member from the viewpoint of easily applying a shear force to the coating film.
[0113] The thickness of the tip of the blade that contacts the coating film is preferably 0.1 mm or more, more preferably 1 mm or more, from the viewpoint of easily applying a shear force to the coating film. There is no upper limit to the thickness of the blade. The thickness of the blade may be determined, for example, within the range of 10 mm or less.
[0114] (shear rate) The shear rate in the second step was 1000 s -1 More than 10000 seconds -1 More preferably, it is 30,000 seconds or more. -1 It is particularly preferable that the shear rate is equal to or higher than 1.0×10. The upper limit of the shear rate is not limited. 6 seconds -1 It may be determined within the following range.
[0115] The method for calculating the shear rate is explained below. For example, when applying shear force using a blade, the shear rate can be calculated by "V / d," where "d" is the shortest distance between the blade and the substrate, and "V" is the transport speed of the coating film that comes into contact with the blade (i.e., the relative speed between the coating film and the blade).
[0116] (Paint surface temperature) The surface temperature of the coating film to which the shear force is applied may be determined according to the phase transition temperature of the liquid crystal compound contained in the coating film. The surface temperature of the coating film to which the shear force is applied is preferably 50°C to 120°C, more preferably 60°C to 100°C. By adjusting the surface temperature of the coating film within the above range, a cholesteric liquid crystal film with high alignment accuracy can be obtained. The surface temperature of the coating film is measured using a radiation thermometer whose emissivity is calibrated by the temperature value measured by a non-contact thermometer. The surface temperature of the coating film is measured in a state where there is no reflective object within 10 cm from the surface opposite to the measurement surface (i.e., the back side).
[0117] (Coating thickness) From the viewpoint of forming a cholesteric liquid crystal film with high alignment accuracy, the thickness of the coating film before the shear force is applied is preferably 30 μm or less, and more preferably in the range of 10 μm to 25 μm.
[0118] From the viewpoint of forming a cholesteric liquid crystal film with high alignment accuracy, the thickness of the coating film after the shear force is applied is preferably 10 μm or less, more preferably 8 μm or less. There is no lower limit to the thickness of the coating film after the shear force is applied. The thickness of the coating film after the shear force is applied is preferably in the range of 5 μm or more.
[0119] [3rd step] The method for producing a cholesteric liquid crystal film according to the present disclosure preferably includes a third step between the first and second steps, in which the solvent content in the applied coating film is adjusted to a range of 50 mass % or less relative to the total mass of the coating film. By adjusting the content of the solvent in the coating film to a range of 50 mass % or less, a cholesteric liquid crystal film with high alignment accuracy can be formed.
[0120] In the third step, the content of the solvent in the coating film is preferably 40% by mass or less, more preferably 30% by mass or less, based on the total mass of the coating film. There is no lower limit for the content of the solvent in the coating film. The content of the solvent in the coating film may be 0% by mass or may exceed 0% by mass, based on the total mass of the coating film. The content of the solvent in the applied coating film is preferably 10% by mass or more, from the viewpoint of easily suppressing deterioration of the surface condition of the applied coating film.
[0121] The content of the solvent in the coating film is measured by the absolute drying method. The specific procedure of the measurement method is explained below. A sample taken from the coating film is dried at 60°C for 24 hours, and then the change in mass of the sample before and after drying (i.e., the difference between the mass of the sample after drying and the mass of the sample before drying) is determined. The above operation is performed three times, and the arithmetic average of the values obtained is taken as the content of the solvent.
[0122] In the third step, an example of a method for adjusting the content of the solvent in the coating film is drying.
[0123] The coating film can be dried by any known drying means, including, for example, an oven, a hot air blower, and an infrared (IR) heater.
[0124] In drying using a hot air blower, hot air may be blown directly onto the coating film, or onto the surface of the substrate opposite to the surface on which the coating film is disposed. A diffusion plate may be provided to prevent the surface of the coating film from flowing due to the hot air.
[0125] Drying may be performed by suction. For drying by suction, for example, a reduced pressure chamber having an exhaust mechanism can be used. By suctioning the gas around the coating film, the content of the solvent in the coating film can be reduced.
[0126] The drying conditions are not limited as long as the content of the solvent in the coating film can be adjusted to a range of 50 mass % or less. The drying conditions may be determined according to, for example, the components contained in the coating film, the coating amount of the coating film, and the conveying speed.
[0127] [4th step] In the method for producing a cholesteric liquid crystal film according to the present disclosure, when the coating liquid contains a polymerizable compound (e.g., a liquid crystal compound having a polymerizable group, or a chiral agent having a polymerizable group), it is preferable to have a fourth step of curing the coating film to which a shear force has been applied after the second step. In the fourth step, the coating film is cured, thereby fixing the molecular alignment of the liquid crystal compound.
[0128] Methods for curing the coating film include, for example, heating and irradiation with active energy rays. In the fourth step, from the viewpoint of manufacturability, it is preferable to cure the coating film by irradiating the coating film to which a shear force has been applied with active energy rays.
[0129] Examples of active energy rays include α rays, γ rays, X-rays, ultraviolet rays, infrared rays, visible light rays, and electron beams. From the viewpoints of curing sensitivity and availability of equipment, the active energy rays are preferably ultraviolet rays.
[0130] Examples of sources of ultraviolet light include lamps (e.g., tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury xenon lamps, and carbon arc lamps), lasers (e.g., semiconductor lasers, helium-neon lasers, argon ion lasers, helium cadmium lasers, and YAG (Yttrium Aluminum Garnet) lasers), light-emitting diodes, and cathode ray tubes.
[0131] The peak wavelength of the ultraviolet light emitted from the ultraviolet light source is preferably 200 nm to 400 nm.
[0132] The amount of UV exposure (also called cumulative light amount) is 100 mJ / cm 2 ~500mJ / cm 2 It is preferable that:
[0133] [Other processes] The method for producing a cholesteric liquid crystal film according to the present disclosure may include steps other than the steps described above. The method for producing a cholesteric liquid crystal film according to the present disclosure may include, for example, a step of forming an alignment layer on a substrate. The step of forming an alignment layer on a substrate is preferably performed before the first step.
[0134] The method for producing a cholesteric liquid crystal film according to the present disclosure may be carried out by a roll-to-roll method, in which, for example, each step is carried out while a long substrate is continuously transported. The method for producing a cholesteric liquid crystal film according to the present disclosure may be carried out using substrates that are transported one by one.
[0135] A method for producing a cholesteric liquid crystal film according to the present disclosure will be described with reference to Fig. 3. Fig. 3 is a schematic diagram showing an example of a method for producing a cholesteric liquid crystal film according to the present disclosure.
[0136] 3, the cholesteric liquid crystal film is manufactured by a roll-to-roll method. A long substrate F wound in a roll shape is transported in the direction of the arrow by a transport roll 500. The transport speed of the substrate F is preferably 10 m / min to 100 m / min.
[0137] The coating liquid is applied to the substrate F that has passed through the transport roll 500 by the coating device 100 (first step). The coating liquid contains a liquid crystal compound, a chiral agent, and a solvent. The coating of the coating liquid by the coating device 100 is carried out in a region where the substrate F is wound around the backup roll 600. A preferred embodiment of the backup roll 600 will be described below.
[0138] For example, hard chrome plating may be applied to the surface of the backup roll 600. The plating thickness is preferably 40 μm to 60 μm.
[0139] The surface roughness Ra of the backup roll 600 is preferably 0.1 μm or less.
[0140] The surface temperature of the backup roll 600 may be controlled within an arbitrary temperature range by a temperature control means. The surface temperature of the backup roll 600 may be determined according to the composition of the coating liquid, the curing performance of the coating liquid, and the heat resistance of the substrate. The surface temperature of the backup roll 600 is preferably, for example, 40°C to 120°C, and more preferably 40°C to 100°C. Examples of the temperature control means for the backup roll 600 include heating means and cooling means. Examples of the heating means include induction heating, water heating, and oil heating. Examples of the cooling means include cooling with cooling water.
[0141] The diameter of the backup roll 600 is preferably from 100 mm to 1,000 mm, more preferably from 100 mm to 800 mm, and particularly preferably from 200 mm to 700 mm.
[0142] The wrap angle of the substrate F with respect to the backup roll 600 is preferably 60° or more, more preferably 90° or more. The upper limit of the wrap angle can be set to, for example, 180°. The "wrap angle" refers to the angle between the transport direction of the substrate when the substrate contacts the backup roll and the transport direction of the substrate when the substrate separates from the backup roll.
[0143] The coating liquid is applied to the substrate F by the coating device 100 to form a coating film, and then the coating film is dried by the drying device 200 (third step). The content of the solvent in the coating film is adjusted by drying the coating film.
[0144] After the coating film is dried by the drying device 200, the upper surface of the coating film that has passed through the transport rolls 510 is scraped off with the blade 300, thereby applying a shear force to the surface of the coating film (second step). The shear force is applied along the conveying direction of the coating film (i.e., the conveying direction of the substrate). The shear force is applied by the blade 300 in the region where the substrate F is wound around the backup roll 610.
[0145] A preferred embodiment of the backup roll 610 is the same as that of the backup roll 600. The surface temperature of the backup roll 610 is preferably, for example, 50°C to 120°C, and more preferably 60°C to 100°C.
[0146] After the shear force is applied to the coating film, the coating film is irradiated with active energy rays from a light source 400 to cure the coating film (fourth step). The coating is cured to form a cholesteric liquid crystal film on the substrate. EXAMPLES
[0147] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to the following examples.
[0148] <Example 1> [Preparing the substrate] A long triacetyl cellulose (TAC) film (FUJIFILM Corporation, refractive index: 1.48, thickness: 80 μm, width: 300 mm) was prepared as a substrate.
[0149] [Formation of alignment layer] A mixture containing pure water (96 parts by mass) and PVA-205 (4 parts by mass, Kuraray Co., Ltd., polyvinyl alcohol) was stirred in a container kept at 80°C to prepare a coating solution for forming an alignment layer. The coating solution for forming an alignment layer was applied onto a substrate (triacetyl cellulose film) using a bar (number: 6), and then dried in an oven at 100°C for 10 minutes. By the above procedure, an alignment layer with a thickness of 2 μm was formed on the substrate.
[0150] [Formation of cholesteric liquid crystal film] A cholesteric liquid crystal film of 8 μm was formed on the alignment layer by the following procedure.
[0151] (Preparation of Liquid Crystal Layer Forming Coating Solution (1)) The components shown below were mixed and then filtered through a polypropylene filter (pore size: 0.2 μm) to prepare a liquid crystal layer-forming coating solution (1).
[0152] -component- (1) Rod-shaped thermotropic liquid crystal compound (compound (A) below): 100 parts by mass (2) Chiral agent (compound (B) below, Palicolor (registered trademark) LC756, BASF): 1.2 parts by mass (3) Photopolymerization initiator 1 (2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, Omnirad 907, IGM Resins BV): 3 parts by mass (4) Photopolymerization initiator 2 (PM758, Nippon Kayaku Co., Ltd.): 1 part by mass (5) Alignment control agent (compound (C) below): 0.5 parts by mass (6) Solvent (methyl ethyl ketone): 184 parts by mass (7) Solvent (cyclohexanone): 31 parts by mass
[0153] Compound (A) is a mixture of the following three compounds, the contents of which in the mixture are, from top to bottom, 84 mass %, 14 mass %, and 2 mass %.
[0154] [ka]
[0155] The chemical structure of compound (B) is shown below.
[0156] [ka]
[0157] The chemical structure of compound (C) is shown below.
[0158] [ka]
[0159] (Coating) The substrate having the alignment layer was heated at 70° C., and then the liquid crystal layer forming coating solution (1) was applied onto the alignment layer using a bar (number: 18).
[0160] (Dry) The liquid crystal layer forming coating solution (1) applied on the alignment layer was dried in an oven at 70° C. for 1 minute to form a coating film with a thickness of 10 μm.
[0161] (Application of shear force) A stainless steel blade heated to 70°C was brought into contact with the coating film while the coating film was heated to 70°C. The blade was then moved at a speed of 1.5 m / min while still in contact with the coating film, and the coating film was subjected to a shear rate of 2500 s -1 The shear force was applied to the blade. The travel distance of the blade was 30 mm. The thickness of the coating film after the shear force was applied was 8 μm.
[0162] (hardening) The coating film subjected to shear stress was exposed to ultraviolet light (exposure dose: 500 mJ / cm) using a metal halide lamp. 2 The coating was cured by irradiation with UV light. FIG. 4 shows a microscope photograph of a cross section in the thickness direction of the cholesteric liquid crystal film of Example 1 obtained as described above.
[0163] <Example 2> The cholesteric liquid crystal film of Example 2 was produced by the same procedure as in Example 1, except that the liquid crystal layer-forming coating solution (2) was used in which the rod-shaped thermotropic liquid crystal compound was changed to the following compound (D).
[0164] The chemical structure of compound (D) is shown below.
[0165] [ka]
[0166] <Example 3> A liquid crystal layer forming coating solution (3) was prepared in the same manner as in Example 1, except that the following components were used.
[0167] -component- (1) Rod-shaped thermotropic liquid crystal compound (compound (A) above): 100 parts by mass (2) Chiral agent (compound (E) below): 1.2 parts by mass (3) Photopolymerization initiator 2 (PM758, Nippon Kayaku Co., Ltd.): 3 parts by mass (4) Photopolymerization initiator 3 (IRGANOX (registered trademark) 1010, BASF): 1 part by mass (5) Alignment control agent (compound (C)): 0.5 parts by mass (6) Solvent (methyl ethyl ketone): 184 parts by mass (7) Solvent (cyclohexanone): 31 parts by mass
[0168] The chemical structure of compound (E) is shown below.
[0169] [ka]
[0170] Next, a cholesteric liquid crystal film of Example 3 was produced using the obtained liquid crystal layer-forming coating solution (3) in the same manner as in Example 1, except that the curing was carried out as described below.
[0171] (hardening) The coating film to which shear stress was applied was exposed to ultraviolet light (exposure dose: 5 mJ cm ) from a high-pressure mercury lamp (HOYA Corporation, UL750) through a long-wavelength cut filter (Asahi Spectroscopy Corporation, SH0325). 2 The coating was cured by irradiation with UV light.
[0172] <Comparative Example 1> The cholesteric liquid crystal film of Comparative Example 1 was produced by the same procedure as in Example 1, except that the thickness of the coating film obtained after drying (i.e., the thickness of the coating film before the application of shear force) was changed to 25 μm, and then the shear force described below was applied. FIG. 5 shows a microscope photograph of a cross section in the thickness direction of the cholesteric liquid crystal film of Comparative Example 1.
[0173] (Application of shear force) A stainless steel blade heated to 110°C was brought into contact with the coating film while the coating film was heated to 110°C. The blade was then moved at a speed of 0.9 m / min while still in contact with the coating film, and the coating film was subjected to a shear rate of 600 s -1The shear force was applied to the blade. The travel distance of the blade was 30 mm. The thickness of the coating film after the shear force was applied was 22 μm.
[0174] [Microscopic observation of cross section in thickness direction] The obtained cholesteric liquid crystal film was cut with a microtome, and a cross-sectional photograph in the thickness direction was taken with a polarizing microscope NV100LPOL manufactured by Nikon Corporation, and the stripe pattern and the folded structure were observed from the photographic image. In addition, the inclination angle of the dark areas in the striped pattern, the distance between the dark areas, and the evenness of spacing (whether the dark areas are arranged at equal intervals) were determined. The results are shown in Table 1.
[0175] [Table 1]
[0176] As is clear from Table 1, when the cholesteric liquid crystal film of the embodiment is observed under a microscope in a cross section in the thickness direction, a striped pattern of alternating dark and light areas and a folded structure of dark areas are seen in the surface layer portion of one of the pair of principal surfaces.
[0177] [Explanation of symbols] 1 Cholesteric liquid crystal film 2. Alignment layer 3 Base material 10 dark side 12 Folding structure with dark areas 20 Akabe 30 Rod-shaped liquid crystal compound 30A molecular axis Fa Principal surface (an example of the other principal surface in a pair of principal surfaces) Fb Principal surface (example of one of a pair of principal surfaces) HA Helical axis 100 Coating device 200 Drying equipment 300 Blade 400 light sources 500, 510 Transport roll 600, 610 Backup roll F Base material
[0178] The disclosure of Japanese Patent Application No. 2020-015748, filed on January 31, 2020, is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated by reference.
Claims
1. It comprises a cholesteric liquid crystal, and In a cross section in the thickness direction observed under a microscope, a striped pattern in which dark and light areas are alternately arranged in one direction, and at an end of the striped pattern, a folded structure of dark areas is present in a surface layer portion of one of a pair of principal surfaces, and a folded structure of dark areas is not present in a surface layer portion of the other principal surface, A cholesteric liquid crystal film in which, in the cross section, the dark areas in the striped pattern are inclined with respect to the main surface and oriented at equal intervals, and the equal intervals are such that the values of the shortest distances between adjacent dark areas measured at five points when calculating the arithmetic mean value of the distances between the dark areas are within ±10% of the arithmetic mean value of the distances between the dark areas.
2. 2. The cholesteric liquid crystal film according to claim 1, wherein the inclination angle of the dark areas in the striped pattern with respect to the principal plane is 20° to 90°.
3. 3. The cholesteric liquid crystal film according to claim 1, wherein the folded structure formed by the dark portions is present in an area extending from the one main surface to 1 / 3 of the film thickness.
4. The cholesteric liquid crystal film according to any one of claims 1 to 3, wherein in the surface layer portion of the one main surface, a folded structure formed by the dark portions is present in 2 to 10 locations among 20 adjacent dark portions.
5. 5. The cholesteric liquid crystal film according to claim 1, wherein in the surface layer of the other of the pair of principal surfaces, the folded structure formed by the dark portions does not exist or exists in less than two places among the 20 adjacent dark portions.
6. A first step of applying a coating liquid containing a solvent, a liquid crystal compound, and a chiral agent onto a substrate to form a coating film; A second step of applying a shear force to the formed coating surface with a blade; having The shear rate in the second step is 2500 s -1 This is the method for producing a cholesteric liquid crystal film.
Citation Information
Patent Citations
Cholesteric layer material with improved color impression and method for manufacturing the same
JP2001172329A
Cholesterol-effect layer and method for manufacturing the same
JP2001515094A
Optical anisotropic film
JP2013120350A
Medium, sticker and transfer foil for preventing forgery and verification method
JP2013233733A
Liquid-crystal film
WO1999034242A1